Caregiver burden and related factors in Iranian mothers of children with attention-deficit hyperactivity disorder - Mina Mostafavi; Hossein Namdar Areshtanab; Hossein Ebrahimi; Maryam Vahidi; Shahrokh Amiri; Sanaz Norouzi (Kashan University of Medical Sciences, 2020)
Background: Literature indicates high levels of burden in primary caregivers of children with attention-deficit hyperactivity disorder (ADHD). Identifying the related factors might help in planning the interventions to reduce it. Objective: This study aimed to identify the caregiver burden and its related factors in Iranian mothers with children suffering from ADHD. Methods: In this correlational study, 246 mothers with children and adolescents suffering from ADHD referred to psychiatric clinics of Tabriz University of Medical Sciences were included through a convenient sampling method. Data were collected using a demographic information form, Zarit Burden Interview, Swanson Nolan and Pelham Parent Rating Scale-IV, and the Kiddie Schedule for Affective Disorders and Schizophrenia-present and lifetime version. Data were analyzed using descriptive statistics, t-test, Pearson's correlation coefficient, analysis of variance, and multiple linear regression analysis. Results: A majority of children (66%) were in the combined subtype. The mean of the disorder severity was 1.91 ± 0.79, 1.76 ± 0.70, and 1.81 ± 0.61 in impulsive, inattentive, and combined subtypes, respectively. The mean of mothers' caregiver burden was 40.43 ± 1.38. A significant relationship was found between the mean severity of the disorder subtypes and caregiver burden. The correlation coefficient was 0.36, 0.29, and 0.29 for the impulsive, inattentive, and combined subtypes, respectively. The mother's age, existence of ADHD in the child's brother, family member's cooperation in caregiving, and the child's birth rank could significantly predict the caregiver burden. Conclusion: Given the role of family-related factors in the burden of care in mothers of children with ADHD, family-centered care and home visits are recommended to assist mothers of these children.